A Study to Assess the Effectiveness of IEC Strategy on Anaemia Among Pregnant Women on Iron Supplementation in A Selected Hospital, Gurugram, Haryana - Sarkar, Manidipa; Sharma, Sushmita; Priya, Sneha; Pradhan, Tripti Rekha (Journal of Neonatal Surgery, 2025)
Background of the study: Pregnant women may benefit from information, education and communication strategies to improve and maintain their health and prevent sickness. Goal: This study aimed to identify the effectiveness of the IEC strategy on iron supplementation for anaemia among pregnant women. Methods: A Quantitative research design was carried out at the SGT Hospital. The subjects were antenatal mothers attending antenatal clinics in SGT Hospital, which was used with a purposive sampling technique, and the Sample size was 120 pregnant mothers. The intervention was provided to the antenatal mothers through a PowerPoint presentation, an information booklet and communication. For selecting the samples, the inclusion and exclusion criteria were followed. A structured questionnaire was used to assess the effectiveness of the IEC strategy on anaemia among pregnant women in selected hospitals. The data gathered was analysed and interpreted using both descriptive and inferential statistics. Results: Among 120 pregnant women in the pre-test, 26.6% had poor knowledge, 14.6% had average knowledge and 26.6% showed good knowledge. After providing intervention, there was an increase in knowledge, with 53.3% showing average knowledge, 33.3% showing good performance, and 13.3% showing excellent performance. Conclusion: After the intervention, there was an increase in the understanding of pregnant women. The IEC strategy was beneficial in improving the knowledge and prevention of anaemia among pregnant mothers. It is advised that health education be provided to antenatal mothers to enhance their knowledge.